PENGARUH TINGKAT PENDIDIKAN IBU TERHADAP KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN DI TK DWI KARYA TANJUNG KOTO KAMPAR HULU - Lestar, Sri Melita Lestar Melita Lestar; Indarto, Wusono Indarto; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The perposes of research were to know the effect of mother education level koward ability of children tongue 5-6 years old TK Dwi Karya Tanjung Koto Kampar Hulu. Population and sample in this research is 50 student consists of 3 mother’s  education level of TK Dwi Karya Tanjung Koto Kampar Hulu. Data collection technigues used observation and interview the technigues analis of data appled formula presentage. The result of this research shows that atility children langue overall  is 63,6% good criteria. Education mother base is 60,46% suffient criteria, medium education mother is 61,78% good criteria, and then highly education mother is 73,03% good criteria. The result of analisis shows that mother’s education level not affect the ability of children tongue TK Dwi Karya Tanjung Koto Kampar Hulu. Data analisis shows that result of calculation chi square is 9,28. If compared with the value of grade chi square on table dk 22 at a significant level 5% abtainable 33,924. Whereas the result of calculation chi square smaller than the result of chi square on the table (9,28>33,924). Key Word: the mother’s education level, ability of children’s tangue